The effect of Virtual Reality Cycling with Music on simple obesity in college students: evidence from a randomized controlled trial in China - Zhao, Meng; Lei, Ying; Wei, Ziran; You, Ming (Frontiers in Public Health, 2024)
BackgroundSimple obesity has become an increasingly prevalent health concern among college students. Existing research indicates that traditional exercise methods may not sufficiently engage this population, particularly those facing barriers to regular physical activity. Thus, this study investigated how combining VR cycling with music influenced fat reduction in this population.MethodThis study recruited 78 Chinese college students with simple obesity (BMI ≥ 28 kg/m2) and randomly assigned them to either an experimental group (VR cycling combined with music, n = 41) or a control group (traditional cycling, n = 37). Both groups engaged in 12 weeks of cycling training, three times a week, for 45 min per session. Key physiological indicators, such as weight, BMI, waist circumference, and hip circumference, were measured at baseline, mid-intervention, and post-intervention.ResultsThe VR cycling with music group exhibited significant improvements in key physiological metrics compared to the control group. Notable changes included a 4.1% reduction in weight, a 2.8% decrease in BMI, and a 2.8% reduction in waist circumference. Hip circumference also decreased by 2.5%, while the waist-to-hip ratio dropped by 0.016 units. Furthermore, the intervention led to a 7.2% increase in vital capacity, with all outcomes showing statistical significance (p<0.01). The experimental group also reported higher levels of enjoyment and engagement throughout the intervention period.ConclusionParticipants in the experimental group experienced significant reductions in weight, BMI, and both waist and hip circumferences, as well as a notable improvement in vital capacity. The study highlights that combining virtual reality cycling with music resulted in more substantial weight loss and fat reduction in obese college students, compared to traditional cycling methods.